FACTORS AFFECTING THE FIRM VALUE OF PROPERTY AND REAL ESTATE COMPANIES: EVIDENCE FROM INDONESIA AS LISTED ON THE INDONESIAN STOCK EXCHANGE - Salomon Parlindungan; Vera Intanie Dewi (Econosains Jurnal Online Ekonomi dan Pendidikan, 2022)
The purpose of this paper is to examine the factors affecting firm value of property and real estate companies in Indonesia. This study is to estimate the relationship between asset structure, profitability, liquidity, firm size, and firm value. Property with an emphasis on housing development and construction, besides being one of the sectors that absorbs many workers, also has a long multiplier effect. This study investigates the factors affecting firm value listed on the Indonesian Stock Exchange. This research is based on four independent variables with four measurements that were empirically examined for their relationship with firm value. These variables are asset structure (as measured by Fixed Asset Ratio/FAR), profitability (Return on Asset/ROA), liquidity (Current Ratio/CR), firm size (Log Natural Total Asset), and firm value (as measured by Price to Book Value (PBV). The population of this research was property and real estate companies listed on the Indonesian Stock Exchange (IDX) in 2017–2020. Data of eighteen property and real estate companies listed on the Indonesia Stock Exchange from 2017–2020 have been extracted from companies’ annual reports. Pooled ordinary least squares regression and fixed effects or random effect models have been used to analyze the data. The findings show that the asset structure as measured by Fixed Asset Ratio (FAR), profitability (ROA), and firm size (SIZE) has a significant effect on firm value. While liquidity (CR) has no significant effect on firm value (PBV). Furthermore, the regression coefficient of Return on Assets provides the largest contribution to firm value. Due to data availability, the data include only property and real estate companies listed in the Indonesian Stock Exchange. This study may not have included all important financial and stock market performance indicators. These results benefit not only for internal users such as managers, shareholders, and employees but also for investors, creditors as external users. For internal users this result is beneficial to the determinants of enhancing the firm value of their company. For external users also may gain advantages from these results to make financial decisions. It is clear that a significant impact happened upon this new policy implementation, and on how Indonesian property and real estate companies increase their firm value in the future. This study differs from previous one in many ways; first, it focuses on property and real estate companies in Indonesia. Previous studies have concentrated on different countries and companies in other sectors, such as manufacturing, banking, and other industrial organizations. Second, this study analyzes the data from property and real estate companies’ annual reports from 2017 to 2020. Third, the study has made use of FAR, ROA, CR and TA as indicators of fundamental factors. Finally, the results of the study provide empirical evidence that firms with a degree of asset structure, profitable operations, and adequate company size, ultimately enhance firm value.